A Semiotic Investigation of the Porta Mariae as a Religious Monumental Architecture - Diaz, Manuel Jr (Journal of Architectural Research and Design Studies, 2025)
The Philippines, a predominantly Catholic country, holds religious monumental architecture (RMA) as a vital part of its cultural and spiritual heritage. This notwithstanding, little academic focus has been given to the meanings conveyed through such structures. This study examines the Porta Mariae in Naga City using Greimassian semiotics, a framework built upon structuralist semiotics for decoding architectural communication. This neoclassical arch, built a little over a decade ago to commemorate 300 years of Bikolano devotion to Our Lady of Peñafrancia and inspired by Roman triumphal arches and Catholic holy doors, has become a prominent city landmark and integral to Catholic rituals in Naga. This paper interprets the structure as a symbolic communication system, uncovering layers of meaning conveyed to pilgrims, devotees, and visitors that extend beyond its visual and architectural appeal. The investigation ultimately reveals the Porta Mariae as a dynamically communicative artifact embodying profound religious, cultural, and historical meanings, serving as a living symbol of Bicolano faith, heritage, and enduring identity.